Eating disorders in athletes: Overview of prevalence, risk factors and recommendations for prevention and treatment - Bratland-Sanda, S.; Sundgot-Borgen, J. (European Journal of Sport Science, 2013)
The prevalence of disordered eating and eating disorders vary from 0-19% in male athletes and 6-45% in female athletes. The objective of this paper is to present an overview of eating disorders in adolescent and adult athletes including: (1) prevalence data; (2) suggested sport- and gender-specific risk factors and (3) importance of early detection, management and prevention of eating disorders. Additionally, this paper presents suggestions for future research which includes: (1) the need for knowledge regarding possible gender-specific risk factors and sport- and gender-specific prevention programmes for eating disorders in sports; (2) suggestions for long-term follow-up for female and male athletes with eating disorders and (3) exploration of a possible male athlete triad.